The role of mouse mesenchymal stem cells in differentiation of naive T-cells into anti-inflammatory regulatory T-cell or proinflammatory helper T-cell 17 population - Svobodová, Eliška; Krulová, Magdaléna; Zajícová, Alena; Pokorná, Kateřina; Procházková, Jana; Trosan, Peter; Holan, Vladimír (Stem cells and development, 2012)
Bone marrow-derived mesenchymal stem cells (MSCs) modulate immune response and can produce significant levels of transforming growth factor-β (TGF-β) and interleukin-6 (IL-6). These 2 cytokines represent the key factors that reciprocally regulate the development and polarization of naive T-cells into regulatory T-cell (Treg) population or proinflammatory T helper 17 (Th17) cells. In the present study we demonstrate that MSCs and their products effectively regulate expression of transcription factors Foxp3 and RORγt and control the development of Tregs and Th17 cells in a population of alloantigen-activated mouse spleen cells or purified CD4(+)CD25(-) T-cells. The immunomodulatory effects of MSCs were more pronounced when these cells were stimulated to secrete TGF-β alone or TGF-β together with IL-6. Unstimulated MSCs produce TGF-β, but not IL-6, and the production of TGF-β can be further enhanced by the anti-inflammatory cytokines IL-10 or TGF-β. In the presence of proinflammatory cytokines, MSCs secrete significant levels of IL-6, in addition to a spontaneous production of TGF-β. MSCs producing TGF-β induced preferentially expression of Foxp3 and activation of Tregs, whereas MSC supernatants containing TGF-β together with IL-6 supported RORγt expression and development of Th17 cells. The effects of MSC supernatants were blocked by the inclusion of neutralization monoclonal antibody anti-TGF-β or anti-IL-6 into the culture system. The results showed that MSCs represent important players that reciprocally regulate the development and differentiation of uncommitted naive T-cells into anti-inflammatory Foxp3(+) Tregs or proinflammatory RORγt(+) Th17 cell population and thereby can modulate autoimmune, immunopathological, and transplantation reactions.
Keywords: Paracrine Communication; imunita; Inflammation; regulační T-lymfocyty; Culture Media, Conditioned; cytokiny; buněčná diferenciace; parakrinní signalizace; buněčné kultury; kultivační média speciální; T-lymfocyty; zánět; T-Lymphocytes, Regulatory; Animals; zvířata; Cell Culture Techniques; myši; Immunity; Cytokines; T-Lymphocytes; Mice; Mesenchymal Stem Cells; Cell Differentiation; mezenchymální kmenové buňky